Pengaruh Pendaftaran Tanah terhadap Keamanan Hak Kepemilikan di Bangka Belitung dalam Perspektif Hukum Perdata - Hervienna Ayu Patricia Utari; Endang Sapitri; Angel Caroline; Sintong Arion Hutapea (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Land registration is an important part of Indonesia's land system that aims to provide legal certainty over land ownership rights. Although this system has been widely implemented, land disputes remain a significant problem in various regions, including in Bangka Belitung. This study aims to examine the role of land registration in providing legal security for land ownership rights in Bangka Belitung as well as the factors that cause land disputes despite land registration. Based on this research, it can be concluded that although land registration provides strong legal protection, there are still various factors that cause land disputes, such as inaccurate registration data, unauthorized transfer of rights, claims based on customary rights, and lack of public understanding of the importance of proper land registration. In addition, the implementation of a more transparent, accurate, and technology-based land registration as well as increased education to the community can help reduce land disputes in Bangka Belitung. This study suggests the importance of improving the land registration system and inclusive dispute resolution efforts, to ensure that land registration can be more effective in providing legal certainty and preventing future conflicts.